Japan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2009)
This Selected Issues paper focuses on Japan's public debt and the challenges facing small- and medium-size enterprises in Japan. Historically, Japan's public debt has been financed in a fairly smooth manner. The large pool of household savings and the stable domestic institutional investor base appear to have contributed to this successful experience. However, Japan is already undergoing rapid population aging, which will likely limit the market's future absorptive capacity of public debt. In addition, structural shifts in institutional investors could also serve to reduce market demand.